On-line spectroscopic and spectrometric methods for the determination of metal species in industrial processes - Monkhouse, Penelope (Progress in energy and combustion science, 2011)
The status of on-line methods for determining metal species, particularly alkali and heavy metals, is reviewed. The background and motivation is discussed first, including current environmental and economic issues associated with release of metal species in industrial processes as well as control measures. Then general diagnostic problems such as optical access and sampling design are considered, followed by an overview of selected diagnostic methods, including recent contributions to technique development and to the understanding of fundamental combustion processes. The main focus is on absorption (tunable diode laser and differential absorption spectroscopies) and emission (spontaneous atomic emission, laser induced fluorescence, photofragment fluorescence as well as several varieties of plasma spectroscopy), but on-line ionisation methods (molecular beam and single particle mass spectrometry and surface ionisation) are also reviewed briefly. In the final section, the capabilities of the selected methods are illustrated by examples of field measurements in the conversion of solid fuels as well as waste incineration, glass production and other processes.
First published online: 23 June 2010
Gesehen am 07.09.2022